2010
DOI: 10.1007/s12105-010-0212-4
|View full text |Cite
|
Sign up to set email alerts
|

Trabecular and Psammomatoid Juvenile Ossifying Fibroma of the Skull Base Mimicking Psammomatoid Meningioma

Abstract: Ossifying fibroma (OF) is a fibro-osseous tumor that usually occurs in young people and arises in the craniofacial bones. We report a case of a 15-year-old boy who developed progressive proptosis and hypertelorism and was found to have a mid-face and skull base tumor, initially diagnosed as psammomatoid meningioma. The tumor recurred and the resected specimen revealed a unique OF having trabecular and psammomatoid features. The clinical, radiographic, histopathologic findings and differential diagnoses of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 16 publications
2
37
0
Order By: Relevance
“…The juvenile psammomatoid variant is characterized by a proliferation of benign spindle-shaped fibroblastic cells with embedded mineralized structures, which may present with round to ovoid collections of bone with an osteoid rim. [12] Multinucleated osteoclast-like giant cells may be seen with occasional normal mitotic figures, but atypia is not a usual feature. [13] Microcopically, the trabeculae variant is composed of a fibroblastic spindle cell stroma, containing osteoid matrix surrounded by osteoblasts and anastomosing trabeculae of immature woven bone, often intermixed with scattered clusters of multinucleated giant cells; mitoses may be present, but cystic degeneration is rare.…”
Section: Discussionmentioning
confidence: 99%
“…The juvenile psammomatoid variant is characterized by a proliferation of benign spindle-shaped fibroblastic cells with embedded mineralized structures, which may present with round to ovoid collections of bone with an osteoid rim. [12] Multinucleated osteoclast-like giant cells may be seen with occasional normal mitotic figures, but atypia is not a usual feature. [13] Microcopically, the trabeculae variant is composed of a fibroblastic spindle cell stroma, containing osteoid matrix surrounded by osteoblasts and anastomosing trabeculae of immature woven bone, often intermixed with scattered clusters of multinucleated giant cells; mitoses may be present, but cystic degeneration is rare.…”
Section: Discussionmentioning
confidence: 99%
“…[13] Rarely these lesions occur as a part of syndrome along with primary hyperparathyroidism designated as 'Hyperparathyroidism-Jaw tumor syndrome' (HPT-JT). [14] Genetic studies showed the presence of nonrandom chromosome break points at Xq26 and 2q33 resulting in (X; 2) translocation. [12][13][14] The recommended treatment is surgical excision.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…[14] Genetic studies showed the presence of nonrandom chromosome break points at Xq26 and 2q33 resulting in (X; 2) translocation. [12][13][14] The recommended treatment is surgical excision. Recurrences in the range of 30 to 50% have been reported, mainly due to incomplete excision.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…A C C E P T E D ACCEPTED MANUSCRIPT 10,13,20 Of course, ground-glass opacity is not unique to JPOF. It is a radiographic feature traditionally associated with fibrous dysplasia.…”
Section: A N U S C R I P Tmentioning
confidence: 99%